Digital Factors Influencing Small and Medium-Sized Businesses in the Context of COVID - R. S. Makasheva; L. A. Tussupova (Экономика: стратегия и практика, 2022)
Education has become an important mechanism in the goal of gender equality achievement. For many decades, access to education was one of the key issues for women. These days it is an issue of not only developing countries but of developed ones as well. Women have become more active in higher education, especially in achieving master degree or PhD. This is due to that public policies are directed at the improvement of the structure of higher education. It includes promotion of human resources diversification among academic staff. This article studies the vision of women regarding higher education. What is the importance of it? This is especially carrier opportunities in higher education. It also discusses carrier opportunities for women in other fields, which has influence on women desire to continue their education. What influence does it have on private life? Higher education also covers state of selfdevelopment, personal improvement and family relationships. The study was provided under the framework of social behavior communication change, which includes four key factors of social behavior. There was conducted a semistructured interview among women. For the interview analysis, Dedoose software was used. According to the results of the study, there have been identified two main factors, which have a great Impact on women participation in higher education. These factors are cultural standard family issues. Major outcomes of higher education for women: potential realization, promotion of women rights. This determines the importance of social behavior in the development of a policy, development of laws and regulations.